The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1093/ndt/11.supp5.2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products in the peritoneal fluid and in the peritoneal membrane of continuous ambulant peritoneal dialysis patients

Abstract: In patients on continuous ambulant peritoneal dialysis (CAPD) treatment, the peritoneal membrane is continuously exposed to the high glucose concentration contained in the dialysate. This may lead to the local generation of advanced glycation end-products (AGEs). To test this hypothesis we evaluated the plasma and dialysate AGE concentrations in five CAPD patients. The dialysate was measured after a 1 h and after a 12 h dwell time. Additionally, in two patients an immunohistochemical investigation of the perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…In comparison to sugars, GDPs have a much higher reactivity towards proteins (glycation), leading to the formation of advanced glycation end-products (AGEs) (Tauer et al, 2001;Millar et al, 1998;Schalkwijk et al, 1999). AGEs accumulate in the peritoneum of patients undergoing CAPD, a process which correlates with the progression of interstitial fibrosis and vascular sclerosis (Mahiout et al, 1996;Nakayama et al, 1997;Honda et al, 1999). Furthermore, GDPs and heat sterilized PD fluids showed a cytotoxic activity against peritoneal mesothelium cells in vitro (Witowski et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to sugars, GDPs have a much higher reactivity towards proteins (glycation), leading to the formation of advanced glycation end-products (AGEs) (Tauer et al, 2001;Millar et al, 1998;Schalkwijk et al, 1999). AGEs accumulate in the peritoneum of patients undergoing CAPD, a process which correlates with the progression of interstitial fibrosis and vascular sclerosis (Mahiout et al, 1996;Nakayama et al, 1997;Honda et al, 1999). Furthermore, GDPs and heat sterilized PD fluids showed a cytotoxic activity against peritoneal mesothelium cells in vitro (Witowski et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, advanced glycation end (AGE) products perform their receptor‐mediated effects by a ROS‐dependent activation of mitogen‐activated protein kinase (12,13). PD causes increased burden of AGEs to the peritoneum (14–18). Induction of intracellular antioxidative molecules, like MT, can offer some prevention against the damages related to AGE (19).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Morgan et al [30]have reported that GDPs, especially formaldehyde and 3,4-di-deoxyglucosone-3-ene (3,4-DGE), impair the mesothelial repair, independent of effects on cell viability or glucose concentration in a scratch-wounding model. Moreover, a few kinds of GDPs accelerate formation and accumulation of AGEs, followed by dysfunction of the peritoneal membrane in PD therapy [3, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the acute toxicity of GDPs contained in PD solutions is limited, a large body of data has demonstrated that exposure of the peritoneal membrane to a low level of GDPs over a long period results in structural and functional changes. Moreover, it has been reported that GDPs in the peritoneum contribute to the formation of advanced glycation end-products (AGEs), which affect the morphology and function of the peritoneum [3, 4]. The accumulation of AGEs accelerates peritoneal permeability and thus causes an ultrafiltration failure [5].…”
Section: Introductionmentioning
confidence: 99%